The Ecologia and Abbasid's Community/ Historical-Ecological Study (Journal of the College of Education for Women, 2018)
The study includes the relationship between the ecologia and Abbaside's community in the middle ages, and the role of Baghdad capital city to increasing the sensibility of the people to the outwardly peripheral.The study explains the efforts between the people and Abbaside's government to cure the knowledge of ecologia, to prevent the separation of diseases and pollutions of the community. Keywords: Ecologia, Abbasid's, diseases, pollutions.